Characterization of Staphylococcus aureus infections in children with Down syndrome. Issue 11 (November 2015) - Johnston, Jeffrey N.; Kaplan, Sheldon L.; Mason, Edward O.; Hulten, Kristina G.
Abstract Staphylococcus aureus infections in the Down syndrome (DS) population have not been well characterized. This study determined clinical and molecular characteristics of S. aureus infections in children with DS followed at Texas Children's Hospital (TCH), from 2001 to 2011. Patients were retrospectively identified from an ongoing S. aureus surveillance study. Medical records were reviewed. Isolates were characterized by antimicrobial susceptibility, pulsed-field gel electrophoresis patterns, and detection of PVL genes (pvl), mupA (high-level mupirocin resistance gene), smr (chlorhexidine resistance conferring gene), and Staphylococcal Chromosomal Cassette mec (SCCmec) type. Twenty-six patients with DS had a total of 34 S. aureus infections (8 recurrent); 61% were MRSA. DS patients represented 16.8 per 10, 000 community onset S. aureus infections seen at TCH. Among 26 initial infections 17 were skin and soft tissue (SSTI), 7 were outer or middle ear and 2 were invasive infections. Seventeen patients were hospitalized. Thirteen (65%) of 20 available isolates were USA300, 14 were pvl+, 5 were mupA+, and 8 were smr+. Five of 8 (63%) recurrent infections were ear infections. All 4 recurrent ear isolates available for study were smr+, ciprofloxacin non-susceptible and treated with ciprofloxacin otic drops. S. aureus infections among patients with DS were similar in presentation to other patient groups, except for a greater proportion being associated with ear infections. Seventy percent of ear fluid isolates carried antiseptic and fluoroquinolone resistance genes. A study of a greater number of DS patients is warranted to further explore these findings.